Character of Housewives According to Islamic Education: A Qualitative Study - Dewita (MANDAILING GLOBAL EDUKASIA, 2024)
Character of the Housewife According to the Concept of Education in the Islamic Perspective. The mother is the first madrasa for her children, the place where the child receives care and is given the first education, perhaps even from the time of conception. A mother consciously or unconsciously has given education to the baby since the womb can already hear and even feel the mood of the mother, so it is not surprising if the emotional bond between mother and child appears more than that of the father. The purpose of this research is to find out the character of the housewife that is in accordance with the concept of Islamic education in the construction of the character of the housewife. To achieve this goal, a descriptive method was used. library research techniques were used. After conducting research, it was found that housewives have the character of an educator for their children. As the first teacher in the family, housewives are obliged to provide education to their children in accordance with Islamic guidelines. The child's education given by the mother should start from the time the child is in the womb, because the baby in the womb is still very sensitive to the stimulation given from the outside. Until when a child is born, he becomes a child who is able to understand religious knowledge. According to the concept of Islamic education, building the character of housewives should be done when mothers are unmarried. Because educating teenagers in accordance with religious guidance means educating future mothers. The education given to housewives includes faith education, worship education and moral education. Through these three educations, housewives can become teachers and role models for their children in the household.